Dogs Therapy for Children with Motor Disabilities - Rashikj Canevska, Olivera; Ramo Akgün, Nergis (DAMOR Toplum Araştırmaları Merkezi, 2021)
Dog therapy is the application of specially trained dogs to achieve general well-being or treatment in different categories of disabilities. Like other animals used for therapeutic purposes, dogs accept, offer comfort, do not condemn and are a great companion during treatment and therapy. Dog therapy builds on the prior existing connection between humans and animals. Engaging with a friendly dog can enable improvements in many physical and mental difficulties. It can help decrease blood pressure and improve the cardiovascular health in general. It can release endorphins, too which ensue a calming effect. This can help ease pain, decrease stress, and enhance child’s psychological state in general. Dog therapy can be used in various ways. Determined objectives are significant part of the therapy, and the progress should be registered with follow up during the structured sessions. The aims of the dog therapy programs involve: enriching motor skills and synchronized movement, reinforcing assisted or autonomous movement, increasing self-esteem, enriching verbal communication, improving the social skills development, increasing the desire to join in activities, enriching interactions with others, stimulating the determination to exercise. This research is a qualitative study that aimed to investigate the effect of dog therapy on students with motor disabilities. The realization of the research took place within three months. The research was conducted in children with motor disabilities, between the ages of 7 and 8 by a special educator and experienced trainer at the Special Center for dog therapy in Skopje, Republic of North Macedonia. The research was organized as a case study format. Researches indicate that the presence of a dog during the therapies leads to improvement in children mood, enrichment in their will to actively participate during the treatments, expression of emotions easily, improvement in communication and psychomotor development and achievement of a range of physiological benefits.
Keywords: therapy, assistance dogs, disability, motor development.